Implementation of a 200 kVA Kiosk-Type Substation on the 20 kV Distribution Network: A Case Study on SM3 Feeder, Tomohon Main Substation - Mario Marcello Rares; Rembulan Sefrida Pongantung; Sasha Agnesia Walukow; Arnold Robert Rondonuwu; Yoice Rita Putung (Jurnal Impresi Indonesia, 2026)
A kiosk substation is a compact, prefabricated enclosure constructed from steel or fiberglass that houses a complete distribution unit, including a medium-voltage cubicle, distribution transformer, and low-voltage switchgear. Its compact and enclosed design offers significant advantages in installation speed, operational safety, space efficiency, and visual aesthetics compared to conventional open-rack pole substations. This study analyzed the implementation of a 200 kVA kiosk-type substation on the 20 kV distribution network of the SM3 Feeder at Tomohon Main Substation (GI Tomohon), and evaluates its contribution to improving the orderliness and performance of the electrical infrastructure in the urban area of Tomohon City. The methodology encompasses a comprehensive literature review, direct field observation along Jl. Kompleks Rindam Kakaskasen to Stadion Babe Palar, collection of technical data including installed transformer capacities, network lengths, and component inventories, as well as structured interviews with technical staff of PT PLN (Persero) UP3 Manado. Field data reveals that the SM3 Feeder currently serves 11 distribution substations with a total medium-voltage network length of 2,758 m using A3CS conductors. The existing substations include 2 cantilever-type, 7 portal-type, and 2 concrete-type units, with a combined installed capacity of 1,760 kVA. Analysis indicates that two 50 kVA substations are approaching their optimal loading limits and are prioritized for replacement. Implementation of 200 kVA kiosk substations is demonstrated to reduce voltage drop from a range of 5-8% to below 3%, optimize transformer loading efficiency, and substantially simplify installation and maintenance procedures.